Los Procesos De Evaluación Y Su Incidencia En El Desempeño Docente En La Escuela Fiscal Mixta “Gran Colombia” De La Parroquia Puerto Pechiche, Cantón Puebloviejo, Provincia Los Ríos. - Ponte Macías., Lidia De Las Mercedes (2014)
The teacher performance evaluation can become a valuable tool for management in educational institutions through work in a context of continuous improvement; hence the need to investigate the impact of evaluation processes on teacher performance in School Fiscal Mixta "Gran Colombia" parish Puerto Pechiche Region Puebloviejo province Rivers. The methodology applied tube having a qualitative method - quantitative, and was descriptive and bibliographical directed to institutional staff, the sample according to the statistical formulation was 217 students, 19 teachers and one director, using tools such as survey research and interview after their applicability is concluded that the school does not have its own internal assessment instruments to determine the level of teacher performance and evaluation that is done is inclined to learning. The approach involved the development of a proposed matrix of teacher performance evaluation for improving educational quality in the Fiscal school "Gran Colombia" Puerto Pechiche parish, as well to evaluate a teaching involves observing their work in the classroom, review how prepared their lessons and feedback to students. Therefore, the best ways to evaluate teacher performance are variations of the art portfolio of evidence, therefore includes the form for portfolio assessment. Keywords: assessment, teacher performance, portfolio.